Carborane‐Based Carbonic Anhydrase Inhibitors1. Issue 51 (4th November 2013) - Brynda, Jiří; Mader, Pavel; Šícha, Václav; Fábry, Milan; Poncová, Kristýna; Bakardiev, Mario; Grüner, Bohumír; Cígler, Petr; Řezáčová, Pavlína
<x xml:space="preserve">Abstract</x> CA inhibitors: Human carbonic anhydrases (CAs) are diagnostic and therapeutic targets. Various carborane cages are shown to act as active‐site‐directed inhibitors, and substitution with a sulfamide group and other substituents leads to compounds with high selectivity towards the cancer‐specific isozyme IX. Crystal structures of the carboranes in the active site provide information that can be applied to the structure‐based design of specific inhibitors.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>